Annual Address to the Board of Governors, September 12, 1955 - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the International Bank for Reconstruction and Development, stated that the Bank, as it enters its tenth year, is going forward in the same spirit of exploration and innovation that has marked its life up to now. Against the always pressing problem of how to raise production and standards of living, we are moving in new, and we hope, constructive ways. The Bank established the Economic Development Institute, a staff college for senior officials in less developed countries. The Bank is now collecting information on credit transactions to better assess risk. The fact that our times are complex, and that the responsibilities of government have grown, should not obscure the truth that economic progress can continue with full momentum only if individuals and groups of individuals have the greatest possible opportunity to make their own successes, and for that matter, to make their own mistakes. The elevation of living standards has properly become a task of first importance to which governments throughout the world are applying their energies and for which they are mobilizing their resources. It will be a sad circumstance if they should neglect to exploit to the full that most productive attribute of the human race, the spirit of individual enterprise.